2016
DOI: 10.1136/ejhpharm-2016-000972
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal injection of tigecycline in treatment of multidrug-resistantAcinetobacter baumanniimeningitis: a case report

Abstract: The ubiquitous Acinetobacter baumannii is an important and troublesome pathogen of nosocomial infection. Multidrug-resistant A baumannii meningitis is very difficult to treat, usually with high mortality. The disease is generally associated with craniotomy, but rarely with lumbar puncture. However, in our case, a 45-year-old male construction worker suffered multidrug-resistant A baumannii meningitis associated with lumbar puncture. The patient responded poorly to the initial treatment with an intravenous infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Tigecycline CSF concentrations after the usual 100 mg IV dose per day are only 0.035–0.048 mg/L, and increasing the daily dose to 200 mg is not well tolerated [ 101 , 102 ]. Several case reports (N = 14) have been described in the literature of IVT tigecycline in the treatment of infections caused by A. baumannii , K. pneumoniae and K. oxytoca ( Table 3 ) [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. The dosing regimen using IVT ranged from 1 mg q12h to 10 mg q12h.…”
Section: Resultsmentioning
confidence: 99%
“…Tigecycline CSF concentrations after the usual 100 mg IV dose per day are only 0.035–0.048 mg/L, and increasing the daily dose to 200 mg is not well tolerated [ 101 , 102 ]. Several case reports (N = 14) have been described in the literature of IVT tigecycline in the treatment of infections caused by A. baumannii , K. pneumoniae and K. oxytoca ( Table 3 ) [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. The dosing regimen using IVT ranged from 1 mg q12h to 10 mg q12h.…”
Section: Resultsmentioning
confidence: 99%
“…The highest concentration of tigecycline in CSF was measured with the combination of 50 mg IV tigecycline and 1 mg IVT tigecycline (2.886 mg/L). Wang et al 10 reported a case of a 45-year-old man who developed MDR A. baumannii meningitis after a lumbar puncture. A dose of 10 mg IVT tigecycline was administered every 12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Although tigecycline has a rapid distribution into tissues, the concentrations in CSF are low with its intravenous (IV) administration. 10 Therefore, the intraventricular (IVT) usage of tigecycline can be considerable as part of the combined therapy with a carbapenem-containing antibiotic regimen, especially against MDR Klebsi-ella pneumoniae and MDR/XDR Acinetobacter baumannii in adults. However, there have been no randomized controlled trials to evaluate the efficacy of IVT antibiotics for the treatment of central nervous system shunt infections.…”
mentioning
confidence: 99%
“…IVT/IT tigecycline use has recently been described, with success at higher and more frequent doses [88 ▪ ]. The first report describing a reduction of serum and CSF white blood cell count and protein, and CSF clearance of Acinetobacter baumannii , utilized intralumbar tigecycline 10 mg every 12 h [89]. Another case report of IVT tigecycline (5 mg daily) for Klebsiella oxytoca ventriculitis, resulted in CSF concentrations at 6 h that were 15–20 times above the MIC but undetectable at 24 h, suggesting a short tigecycline CSF half-life [88 ▪ ].…”
Section: Intraventricular/intrathecal Antimicrobialsmentioning
confidence: 99%